Constraint of Improved Rice Production Technology by the Farmers in Dungarpur District of Rajasthan - Ram Lal Khatik and B. S. Bhimawat, (Indian Journal of Extension Education, 2015)
India is the second leading producer of rice in the entire world, preceded by China. Rice remains a staple food for themajority of the world's population. More than two-thirds of the world relies on the nutritional benefits of rice. Rice isnaturally fat, cholesterol and sodium free. Rice is primarily a high energy or high calorie food. In Rajasthan rice is grownon an area of 131126 Lakh hectares with a production of 265545 lakh tones (Anonymous, 2010-11). The major ricegrowing districts in Rajasthan are Banswara, Dungarpur, Kota, Bundi, Sriganganagar and Hanumangarh. The presentstudy was conducted in Dungarpur district of Southern Rajasthan. There are total four tehsils in Dungarpur district ofRajasthan, out of which two tehsil namely Simalwara and Dungarpur have been selected on the basis of maximum areaunder cultivation of rice. For selection of respondents total 120 rice growers (60 small and 60 marginal farmers) wereselected on the basis of random sampling method from the identified villages for the present study. It was found that 62(51.67%) of total rice producers faced medium level of constraints in adoption of rice production technology. Whereas, 34(28.33%) respondents were reported from the group of low constraints level and 24 (20.00%) respondents were in the highconstraints level.